Association Between Eating Habits and Perceived School Performance: A Cross-Sectional Study Among 46,455 Adolescents From 42 Countries - López-Gil, José Francisco; Mesas, Arthur Eumann; Álvarez-Bueno, Celia; Pascual-Morena, Carlos; Saz-Lara, Alicia; Cavero-Redondo, Iván (Frontiers in Nutrition, 2022)
Purpose: This study analysed the association between selected eating habits and school performance in adolescents by gender. Methods: A cross-sectional analysis was conducted with data from a large representative sample of adolescents from 42 different countries. Participants answered questions about their weekly frequency of fruit, vegetable, sweets and soft drink consumption, as well as the frequency of breakfast consumption and family meals. The adolescents subjectively rated their school performance compared to that of their classmates. Logistic regression models were adjusted for the main confounders. Results: Among the 46,455 (53.5% female, mean age of 13.7 ± 1.6 years) adolescents studied, 20.6% of males and 25.5% of females reported high perceived school performance. In the results of the fully adjusted analyses, the higher the frequency of all healthy eating habits studied, the higher the perceived school performance in both males and females. Specifically, adolescents reporting a higher frequency of fruit and vegetable consumption, a lower frequency of sweets and soft drink consumption, more frequent breakfast consumption, and more frequent family meals (breakfast and dinner) were more likely to perceive their school performance as higher compared to their classmates. Conclusions: In summary, this study provide strong cross-sectional evidence on the association between healthy eating habits and perceived school performance. Considering that school performance is an indicator of healthy development in adolescence, our findings reinforce and extend the evidence on the importance of healthy eating at this stage of life.